Investigation of modified horizontal wing cut twisted tapes fitted with rod and spacer at trailing edge on heat transfer properties in Double Glazing V-Trough solar water heaters. Issue 7 (28th May 2019) - Gnanaraj, D.; Vijayan, R.
ABSTRACT: An experimental analysis of heat transfer efficiency in double glazing solar water heating system having full-length Horizontal wing cut twisted tapes having twist ratio 3 fitted with rod or spacer of dimensions 125 mm, 250 mm, and 500 mm as length at the trailing edges has been dealt in this work. The experimental results have been compared with a plain tube with similar operating conditions and concluded that variation in the Nusselt number, as well as friction factor, are ±12.56% and ±10.17%, respectively. The result of empirical correlation concludes that Nusselt number is maximal for horizontal wing cut twisted tapes having rod or spacer at its ends while comparing with full-length horizontal wing cut twisted tapes. The friction factor is low for full-length horizontal wing cut twisted tapes than the horizontal wing cut twisted tapes fitted with rod or spacer. The horizontal wing cut twisted tapes fitted with rod has superior performance than twist fitted with spacer.